2004
DOI: 10.1038/sj.ejcn.1602066
|View full text |Cite
|
Sign up to set email alerts
|

Lower resting metabolic rate in the elderly may not be entirely due to changes in body composition

Abstract: Objective: To investigate whether or not the lower resting metabolic rate (RMR) in the elderly is entirely due to changes in body composition. Design: Cross-sectional data of 132 female (age 69.975.5 y, body mass index (BMI) 26.574.0 kg/m 2 ) and 84 male (age 68.975.1 y, BMI 26.172.8 kg/m 2 ) participants of the longitudinal study on nutrition and health status in an aging population of Giessen, Germany, as well as that of 159 young women (age 24.873.0 y, BMI 21.172.5 kg/m 2 ) and 67 young men (age 26.873.4 y,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 43 publications
5
43
1
1
Order By: Relevance
“…This question has been addressed in several cross-sectional studies with inconsistent results. Although some authors could not find significant differences in RMR of young and elderly subjects after adjustment for body composition (Welle et al, 1996;Bosy-Westphal et al, 2003), other studies showed that RMR in elderly subjects was significantly lower in comparison with young adults even after correcting for body composition (Klausen et al, 1997;Gallagher et al, 2000;Hunter et al, 2001;Krems et al, 2005). Results of our investigations show that the decline in RMR is not entirely due to changes in body composition.…”
Section: Discussionsupporting
confidence: 53%
“…This question has been addressed in several cross-sectional studies with inconsistent results. Although some authors could not find significant differences in RMR of young and elderly subjects after adjustment for body composition (Welle et al, 1996;Bosy-Westphal et al, 2003), other studies showed that RMR in elderly subjects was significantly lower in comparison with young adults even after correcting for body composition (Klausen et al, 1997;Gallagher et al, 2000;Hunter et al, 2001;Krems et al, 2005). Results of our investigations show that the decline in RMR is not entirely due to changes in body composition.…”
Section: Discussionsupporting
confidence: 53%
“…When BMR was adjusted for FFM by ANCOVA, it was still lower in Italian volunteers than in middle-aged French subjects (À12%). These results confirm those obtained by other authors (Fukagawa et al, 1990;Visser et al, 1995;Klausen et al, 1997;Das et al, 2001;Krems et al, 2005). It has been postulated that the relationship of BMR to FFM in older individuals can be confounded by a change in the composition of FFM (Bosy-Westphal et al, 2003) and may be mediated by other factors such as sympathetic nervous system activity, thyroid hormone status, uncoupling activity, etc.…”
Section: Discussionsupporting
confidence: 90%
“…The present results agree also with other studies reported that fat mass was increased with age, but contradicts findings reported that there is little or no further gain in fat mass in older age 40-55 [17][18][19][20]. Generally, BMR depends on body composition as expressed by fat-free mass (FFM) and fat mass (FM) and on gender, age, physical activity, and nutritional status [26][27][28]. The lower BMR of older adults may be due in part to slowed organ metabolic rates and this may contribute to changes in FM and FFM.…”
Section: Resultssupporting
confidence: 80%